A geopolymer adsorbent, preparation method and application thereof in zinc-containing wastewater treatment

By preparing geological polymer adsorbents, using their porous channel structure to improve the adsorption capacity of zinc ions, solving the problem of zinc-containing wastewater treatment in the metallurgical industry, and achieving efficient adsorption of zinc ions and high-value utilization of blast furnace slag.

CN119303541BActive Publication Date: 2025-03-18LANZHOU UNIVERSITY OF TECHNOLOGY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411850988.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-18
Estimated Expiration
2044-12-16

Smart Images

  • Figure CN119303541B_ABST
    Figure CN119303541B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of sewage treatment adsorbents, specifically a geopolymer adsorbent, a preparation method and an application thereof in zinc-containing sewage treatment, wherein the components include the following components by mass: 8-14 parts of pretreated calcium carbonate, 42-58 parts of pretreated blast furnace slag, 3-8 parts of polyvinyl alcohol particles, 10-14 parts of sodium hydroxide, and 4-8 parts of nano silicon dioxide. The present invention synthesizes and prepares geopolymers through blast furnace slag, can effectively utilize solid waste, and at the same time, in combination with calcium carbonate powders with different coarse and fine particles, can orderly combine blast furnace slag and calcium carbonate, generate orderly and diverse pore structures inside the prepared geopolymer, and improve the adsorption capacity of the entire material to zinc ions in sewage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sewage treatment adsorbents, in particular to a geopolymer adsorbent, a preparation method and application thereof in zinc-containing sewage treatment. Background Art

[0002] The rapid development of industries such as metallurgy and chemical industry has produced a large amount of wastewater containing heavy metal ions, which has posed a serious threat to the earth's ecological environment and human life and health. The "Opinions on Further Strengthening the Prevention and Control of Heavy Metal Pollution" issued by the Ministry of Ecology and Environment clearly defines the governance goals of heavy metal pollution in key industries across the country, and proposes key tasks for the non-ferrous metal industry, especially the lead and zinc smelting and copper smelting industries in key areas. A large amount of zinc-containing heavy metal wastewater is generated in metallurgical processes such as lead and zinc ore beneficiation and hydrometallurgical zinc smelting, which is seriously harmful to human health and agricultural production.

[0003] Therefore, the comprehensive treatment of heavy metal wastewater has become an urgent problem to be solved and is one of the hot topics in the field of metallurgical environment research. Adsorption is the most widely studied and applied method for treating heavy metal wastewater. As a low-cost new green adsorption material, geopolymers, which have attracted much attention in recent years, have shown extremely high application potential and value in the field of heavy metal wastewater treatment. Blast furnace slag is a type of bulk solid waste in the metallurgical industry. The annual discharge in my country is as high as more than 60 million tons. It is currently mainly used to produce cement, bricks and tiles and other building materials, and the high-value utilization rate is low. Blast furnace slag is an amorphous material with the main components of CaO, MgO, SiO2 and Al2O3, which meets the raw material requirements for the preparation of geopolymers. Therefore, using blast furnace slag to transform geopolymer adsorption materials to treat zinc-containing heavy metal wastewater and realize the comprehensive recovery of metallic zinc can realize the comprehensive utilization of blast furnace slag high-value resources and achieve the purpose of "treating waste with waste and turning waste into treasure", which has important environmental benefits and economic value. Summary of the invention

[0004] The object of the present invention is to provide a geopolymer adsorbent, a preparation method and application thereof in zinc-containing wastewater treatment to solve the problems raised in the above background technology.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A geopolymer adsorbent comprises the following components by weight:

[0007] 8-14 parts of pretreated calcium carbonate, 42-58 parts of pretreated blast furnace slag, 3-8 parts of polyvinyl alcohol particles, 10-14 parts of sodium hydroxide, and 4-8 parts of nano silicon dioxide;

[0008] The pretreated calcium carbonate is prepared by the following steps:

[0009] Grinding calcium carbonate particles through a 600-1000 mesh sieve, uniformly dispersing the sieved calcium carbonate particles into a mixed solution of 3-(2,3-epoxypropoxy)propyltrimethoxysilane and chloroform, stirring for 0.8-2 hours and then filtering, washing the filtered product with sufficient anhydrous ethanol, and drying the washed product at 30° C. to obtain pretreated calcium carbonate;

[0010] The pretreated blast furnace slag is prepared by the following steps:

[0011] Grinding the blast furnace slag through a 300-400 mesh sieve, dispersing the sieved blast furnace slag into a mixed solution of 3-carboxypropyltrimethoxysilane, ethanol and acetone, stirring for 1.6-3.4 hours and then filtering, washing the filtered product with sufficient deionized water, and drying the washed product at 30° C. to obtain pretreated blast furnace slag;

[0012] The polyvinyl alcohol particles are selected from polyvinyl alcohol particles that pass through a 150-200 mesh sieve.

[0013] Furthermore, the mass ratio of the 3-(2,3-epoxypropoxy)propyltrimethoxysilane, the calcium carbonate particles and the chloroform is 1:(2-5):(60-100).

[0014] Furthermore, the mass ratio of the 3-carboxypropyltrimethoxysilane, blast furnace slag, ethanol and acetone is 1:(2-5):(20-40):(30-40).

[0015] A method for preparing a geopolymer adsorbent comprises the following steps:

[0016] S1, mixing pretreated calcium carbonate, pretreated blast furnace slag and polyvinyl alcohol particles to obtain a mixture;

[0017] S2, ultrasonically dispersing nano-silicon dioxide into deionized water to obtain silica sol, dissolving sodium hydroxide into deionized water to obtain sodium hydroxide solution, adding the sodium hydroxide solution into the silica sol, and continuously stirring for 18-26 hours to obtain an alkaline excitation solution;

[0018] S3, adding the mixture obtained in step S1 to the alkali stimulating solution in step S2 to obtain an alkali stimulating product, stirring the alkali stimulating product at high speed for 1-3 minutes and then adding it to the mold;

[0019] S4, drying the alkali-activated substance in the mold in step S3 to obtain a dried product;

[0020] S5. Soak the mold containing the dried product in step S4 in a 0.2 mol / L hydrochloric acid solution, take the mold out of the hydrochloric acid solution, separate the mold, wash the material in the mold with sufficient deionized water, and obtain the geopolymer adsorbent after natural drying.

[0021] Furthermore, in the step S2, the mass ratio of nano-silicon dioxide to deionized water in the silica sol is 1:(3-5), and the mass ratio of sodium hydroxide to deionized water in the sodium hydroxide solution is 1:(6-8).

[0022] Furthermore, the rotation speed of the continuous stirring in step S2 is 80 r / min, and the rotation speed of the high-speed stirring in step S3 is 300 r / min.

[0023] Furthermore, the drying temperature in step S4 is 50-60°C.

[0024] Furthermore, in step S5, the hydrochloric acid solution is heated to 60-90° C., and the mold containing the dried product is immersed in the hydrochloric acid solution for 0.5-2 hours.

[0025] Application of the above geopolymer adsorbent in zinc-containing wastewater treatment.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] 1. The present invention adds pretreated calcium carbonate, and the pretreated calcium carbonate and blast furnace slag are matched with each other in the form of fine particles and coarse particles. The pretreated calcium carbonate is filled between the blast furnace slag, and the calcium carbonate therein is removed during the hydrochloric acid treatment to form a multi-porous structure, so that the entire geopolymer can also quickly absorb zinc ions in the sewage;

[0028] 2. Polyvinyl alcohol is also added in the present invention. When the material is treated with an alkaline stimulating solution, the polyvinyl alcohol can be gelled. The gelation enables the blast furnace slag to maintain the stability of the overall structure to a certain extent when it is dissolved, promotes the uniformity of the distribution of the pretreated calcium carbonate, and thus ensures the orderly formation of pores. Finally, the polyvinyl alcohol is hydrolyzed and removed with the hydrochloric acid treatment, leaving a porous geopolymer. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 A process flow chart for preparing the geopolymer adsorbent of the present invention;

[0030] Figure 2 This is a SEM image of the geopolymer adsorbent prepared in Example 1 of the present invention at a magnification of 2000;

[0031] Figure 3 This is a SEM image of the geopolymer adsorbent prepared in Example 1 of the present invention at a magnification of 5000;

[0032] Figure 4 This is a SEM image of the geopolymer adsorbent prepared in Example 1 of the present invention at a magnification of 10,000;

[0033] Figure 5 This is an EDS surface scan photo of the geopolymer adsorbent prepared in Example 1 of the present invention;

[0034] Figure 6 This is an EDS surface scan photograph of the geopolymer adsorbent prepared in Example 1 of the present invention after adsorbing zinc. DETAILED DESCRIPTION

[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] See also Figures 1 to 6 , the present invention provides a technical solution:

[0037] Example 1

[0038] A method for preparing a geopolymer adsorbent comprises the following steps:

[0039] S1, 10.2 g of pretreated calcium carbonate, 48.5 g of pretreated blast furnace slag and 5.4 g of polyvinyl alcohol particles were mixed to obtain a mixture;

[0040] S2, ultrasonically dispersing 6.1 g of nano-silicon dioxide into 24.2 g of deionized water to obtain a silica sol, dissolving 12.4 g of sodium hydroxide into 87.8 g of deionized water to obtain a sodium hydroxide solution, adding the sodium hydroxide solution to the silica sol, and stirring continuously at a speed of 80 r / min for 25 h to obtain an alkaline excitation solution;

[0041] S3, adding the mixture obtained in step S1 to the alkali stimulating solution in step S2 to obtain an alkali stimulating product, stirring the alkali stimulating product at a high speed of 300 r / min for 2 minutes, and then adding the product to the mold;

[0042] S4, drying the alkali-activated product in the mold in step S3 at 55° C. to obtain a drying product;

[0043] S5. Put the mold containing the dried product in step S4 into a hydrochloric acid solution with a concentration of 0.2 mol / L and heated to 80° C. and soak it for 0.8 h. Take the mold out of the hydrochloric acid solution, separate the mold, wash the material in the mold with sufficient deionized water, and obtain the geopolymer adsorbent after natural drying.

[0044] The above-mentioned pretreated calcium carbonate is prepared by the following steps:

[0045] 12.1 g of calcium carbonate particles were ground through a 1000 mesh sieve, and the sieved calcium carbonate particles were evenly dispersed in a mixed solution of 4.1 g of 3-(2,3-epoxypropoxy)propyltrimethoxysilane and 295.2 g of chloroform, and the mixture was stirred for 1.6 h and then filtered. The filtered product was washed with sufficient anhydrous ethanol, and the washed product was dried at 30° C. to obtain pretreated calcium carbonate;

[0046] The above-mentioned pretreated blast furnace slag is prepared by the following steps:

[0047] 58.4 g of blast furnace slag was ground through a 325 mesh sieve, and the sieved blast furnace slag was dispersed in a mixed solution of 14.6 g of 3-carboxypropyltrimethoxysilane, 365 g of ethanol and 467.2 g of acetone, and the mixture was stirred for 3.2 h and then filtered. The filtered product was washed with sufficient deionized water, and the washed product was dried at 30° C. to obtain pretreated blast furnace slag;

[0048] The polyvinyl alcohol particles are selected from polyethanol particles that have passed through a 175-mesh sieve.

[0049] Example 2

[0050] A method for preparing a geopolymer adsorbent comprises the following steps:

[0051] S1, 8 g of pretreated calcium carbonate, 42 g of pretreated blast furnace slag and 3 g of polyvinyl alcohol particles were mixed to obtain a mixture;

[0052] S2, ultrasonically dispersing 4 g of nano-silicon dioxide into 12 g of deionized water to obtain a silica sol, dissolving 10 g of sodium hydroxide into 60 g of deionized water to obtain a sodium hydroxide solution, adding the sodium hydroxide solution to the silica sol, and continuously stirring at a speed of 80 r / min for 18 h to obtain an alkaline excitation solution;

[0053] S3, adding the mixture obtained in step S1 to the alkali stimulating solution in step S2 to obtain an alkali stimulating product, stirring the alkali stimulating product at a speed of 300 r / min for 1 min, and then adding the product to the mold;

[0054] S4, drying the alkali-activated product in the mold in step S3 at 50° C. to obtain a drying product;

[0055] S5. Put the mold containing the dried product in step S4 into a hydrochloric acid solution with a concentration of 0.2 mol / L and heated to 60° C. and soak it for 0.5 h. Take the mold out of the hydrochloric acid solution, separate the mold, wash the material in the mold with sufficient deionized water, and obtain the geopolymer adsorbent after natural drying.

[0056] The above-mentioned pretreated calcium carbonate is prepared by the following steps:

[0057] 10.2 g of calcium carbonate particles were ground through a 600-mesh sieve, and the sieved calcium carbonate particles were evenly dispersed in a mixed solution of 5.1 g of 3-(2,3-epoxypropoxy)propyltrimethoxysilane and 306 g of chloroform, and the mixture was stirred for 0.8 h and then filtered. The filtered product was washed with sufficient anhydrous ethanol, and the washed product was dried at 30° C. to obtain pretreated calcium carbonate;

[0058] The above-mentioned pretreated blast furnace slag is prepared by the following steps:

[0059] 46.2 g of blast furnace slag was ground through a 300-mesh sieve, and the sieved blast furnace slag was dispersed in a mixed solution of 23.1 g of 3-carboxypropyltrimethoxysilane, 462 g of ethanol and 693 g of acetone, and the mixture was stirred for 1.6 h and then filtered. The filtered product was washed with sufficient deionized water, and the washed product was dried at 30° C. to obtain pretreated blast furnace slag;

[0060] The polyvinyl alcohol particles are selected from polyethanol particles that have passed through a 150-mesh sieve.

[0061] Example 3

[0062] A method for preparing a geopolymer adsorbent comprises the following steps:

[0063] S1, 14g of pretreated calcium carbonate, 58g of pretreated blast furnace slag and 8g of polyvinyl alcohol particles were mixed to obtain a mixture;

[0064] S2, ultrasonically dispersing 8 g of nano-silicon dioxide into 40 g of deionized water to obtain a silica sol, dissolving 14 g of sodium hydroxide into 112 g of deionized water to obtain a sodium hydroxide solution, adding the sodium hydroxide solution to the silica sol, and continuously stirring at a speed of 80 r / min for 26 h to obtain an alkaline excitation solution;

[0065] S3, adding the mixture obtained in step S1 to the alkali activating solution in step S2 to obtain an alkali activator, stirring the alkali activator at a speed of 300 r / min for 3 minutes, and then adding the alkali activator to the mold;

[0066] S4, drying the alkali-activated product in the mold in step S3 at 60° C. to obtain a drying product;

[0067] S5. Soak the mold containing the dried product in step S4 in a 0.2 mol / L hydrochloric acid solution heated to 90° C. for 2 h, take the mold out of the hydrochloric acid solution, separate the mold, wash the material in the mold with sufficient deionized water, and obtain the geopolymer adsorbent after natural drying.

[0068] The above-mentioned pretreated calcium carbonate is prepared by the following steps:

[0069] 16.4 g of calcium carbonate particles were ground through a 1000 mesh sieve, and the sieved calcium carbonate particles were evenly dispersed in a mixed solution of 3.3 g of 3-(2,3-epoxypropoxy)propyltrimethoxysilane and 330 g of chloroform, and the mixture was stirred for 2 h and then filtered. The filtered product was washed with sufficient anhydrous ethanol, and the washed product was dried at 30° C. to obtain pretreated calcium carbonate;

[0070] The above-mentioned pretreated blast furnace slag is prepared by the following steps:

[0071] 62.5 g of blast furnace slag was ground through a 400 mesh sieve, and the sieved blast furnace slag was dispersed in a mixed solution of 12.5 g of 3-carboxypropyltrimethoxysilane, 500 g of ethanol and 500 g of acetone, and the mixture was stirred for 3.4 hours and then filtered. The filtered product was washed with sufficient deionized water, and the washed product was dried at 30° C. to obtain pretreated blast furnace slag;

[0072] The polyvinyl alcohol particles are selected from polyethanol particles that have passed through a 200-mesh sieve.

[0073] Example 4

[0074] A method for preparing a geopolymer adsorbent comprises the following steps:

[0075] S1, 11.8 g of pretreated calcium carbonate, 52.4 g of pretreated blast furnace slag and 5.2 g of polyvinyl alcohol particles were mixed to obtain a mixture;

[0076] S2, ultrasonically dispersing 6.8 g of nano-silicon dioxide into 34 g of deionized water to obtain a silica sol, dissolving 13.6 g of sodium hydroxide into 95.3 g of deionized water to obtain a sodium hydroxide solution, adding the sodium hydroxide solution to the silica sol, and continuously stirring at a speed of 80 r / min for 21 h to obtain an alkaline excitation solution;

[0077] S3, adding the mixture obtained in step S1 to the alkali stimulating solution in step S2 to obtain an alkali stimulating product, stirring the alkali stimulating product at a speed of 300 r / min for 1 min, and then adding the product to the mold;

[0078] S4, drying the alkali-activated product in the mold in step S3 at 55° C. to obtain a drying product;

[0079] S5. The mold containing the dried product in step S4 is placed in a hydrochloric acid solution with a concentration of 0.2 mol / L and heated to 70° C. and soaked for 1.5 h. The mold is taken out of the hydrochloric acid solution, separated, and the material in the mold is washed with sufficient deionized water. After natural drying, a geopolymer adsorbent is obtained.

[0080] The above-mentioned pretreated calcium carbonate is prepared by the following steps:

[0081] 13.1 g of calcium carbonate particles were ground through a 800-mesh sieve, and the sieved calcium carbonate particles were evenly dispersed in a mixed solution of 3.1 g of 3-(2,3-epoxypropoxy)propyltrimethoxysilane and 280 g of chloroform, and the mixture was stirred for 1.2 h and then filtered. The filtered product was washed with sufficient anhydrous ethanol, and the washed product was dried at 30° C. to obtain pretreated calcium carbonate;

[0082] The above-mentioned pretreated blast furnace slag is prepared by the following steps:

[0083] 56.7 g of blast furnace slag was ground through a 325 mesh sieve, and the sieved blast furnace slag was dispersed in a mixed solution of 14.1 g of 3-carboxypropyltrimethoxysilane, 424 g of ethanol and 461 g of acetone, stirred for 3.1 hours and then filtered, the filtered product was washed with sufficient deionized water, and the washed product was dried at 30° C. to obtain pretreated blast furnace slag;

[0084] The polyvinyl alcohol particles are selected from polyethanol particles that have passed through a 200-mesh sieve.

[0085] The present invention uses an X-ray fluorescence spectrometer (XRF) to detect that the main oxides in the blast furnace slag are CaO, SiO2, Al2O3, etc.; quantitative analysis of Si, Al, and Ga elements in the blast furnace slag shows that SiO2 accounts for 34.21%, Al2O3 accounts for 16.67%, and CaO accounts for 29.2%.

[0086] Comparative Example 1

[0087] The difference between Comparative Example 1 and Example 1 is that the addition of pretreated calcium carbonate is eliminated, and the remaining steps are exactly the same as those of Example 1.

[0088] Comparative Example 2

[0089] The difference between Comparative Example 2 and Example 1 is that the addition of polyvinyl alcohol is eliminated, and the remaining steps are exactly the same as those of Example 1.

[0090] Comparative Example 3

[0091] The difference between Comparative Example 3 and Example 1 is that not only the addition of pretreated calcium carbonate is eliminated, but also the addition of polyvinyl alcohol is eliminated.

[0092] Comparative Example 4

[0093] The difference between Comparative Example 4 and Example 1 is that the preparation of pretreated calcium carbonate is limited to grinding calcium carbonate particles, and the preparation of pretreated blast furnace slag is limited to grinding blast furnace slag, and the remaining steps are exactly the same as Example 1.

[0094] Comparative Example 5

[0095] The difference between Comparative Example 5 and Example 1 is that the ground calcium carbonate in the preparation of pretreated calcium carbonate is passed through a 325-mesh sieve, and the remaining steps are exactly the same as those in Example 1.

[0096] 9 groups of geopolymer adsorbents were prepared by Examples 1-4 and Comparative Examples 1-5, and the adsorption capacity of the 9 groups of geopolymer adsorbents was tested respectively;

[0097] The test method is as follows: 9 cups of 800 mg / mL Zn ion solution are prepared with zinc nitrate hexahydrate, 800 mL of the solution is placed in a 1000 mL beaker, 4 g of each of the 9 groups of geopolymer adsorbents prepared in Examples 1-4 and Comparative Examples 1-5 are weighed and added to different beakers containing zinc ion solution and allowed to stand for 4 h (the geopolymer adsorbents cut from each beaker are of the same size and have a regular surface), and the equilibrium concentration of zinc ions in each beaker after adsorption is detected by an inductively coupled plasma optical emission spectrometer (ICP-OES), and the equilibrium adsorption amount of Zn (Q) is calculated by the following formula: e ),

[0098]

[0099] In the formula, Q e is the equilibrium adsorption amount of Zn (mg / g); C0 is the initial concentration of Zn (mg / L); C e is the equilibrium concentration of Zn after adsorption; V is the volume of Zn solution (L); m is the mass of geopolymer (g). The test results are shown in Table 1 below:

[0100] Table 1: Experimental table of zinc ion adsorption by geopolymer adsorbents prepared in Examples 1-4 and Comparative Examples 1-5

[0101]

[0102] According to the data of Example 1 and Comparative Examples 1-3 in Table 1 above, the present invention can form more pore structures inside the geopolymer adsorbent by adding pretreated calcium carbonate and polyvinyl alcohol, thereby improving the adsorption capacity of the geopolymer adsorbent for zinc ions. In addition, the adsorption capacity of the geopolymer adsorbent for zinc ions is further improved by combining fine-particle pretreated calcium carbonate and coarse-particle pretreated blast furnace slag.

[0103] The morphology of the geopolymer adsorbent prepared in Example 1 was studied using a scanning electron microscope (SEM). Figure 2 As shown in the morphology diagram, it is found that the surface and interior of the geopolymer adsorbent contain a large number of pore structures, which greatly increase the adsorption sites of the geopolymer adsorbent and effectively improve the adsorption amount and adsorption efficiency of the geopolymer adsorbent;

[0104] The SEM image of the geopolymer adsorbent prepared in Example 1 is as follows: Figure 2 (2000 times), Figure 3 (5000 times) and Figure 4 (10000 times) as shown; EDS surface scanning photo of the geopolymer adsorbent prepared in Example 1 ( Figure 5 As shown in the figure, it can be observed that the geopolymer adsorbent contains O, Al, Si, and Ca elements. In order to verify that the substance adsorbed on the geopolymer adsorbent is zinc, EDS analysis was performed on the sample after the geopolymer adsorbent adsorbed zinc ( Figure 6 As shown), it was observed that zinc was present on the surface of the geopolymer, which indicated that zinc had been adsorbed on the surface of the geopolymer adsorbent after the adsorption experiment on the geopolymer adsorbent.

[0105] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A geopolymer adsorbent, characterized in that: The raw material composition includes the following components by mass: 8-14 parts of pretreated calcium carbonate, 42-58 parts of pretreated blast furnace slag, 3-8 parts of polyvinyl alcohol particles, 10-14 parts of sodium hydroxide, and 4-8 parts of nano silicon dioxide; The pretreated calcium carbonate is prepared by the following steps: Grinding calcium carbonate particles through a 600-1000 mesh sieve, uniformly dispersing the sieved calcium carbonate particles into a mixed solution of 3-(2,3-epoxypropoxy)propyltrimethoxysilane and chloroform, stirring for 0.8-2 hours and then filtering, washing the filtered product with sufficient anhydrous ethanol, and drying the washed product at 30° C. to obtain pretreated calcium carbonate; The pretreated blast furnace slag is prepared by the following steps: Grinding the blast furnace slag through a 300-400 mesh sieve, dispersing the sieved blast furnace slag into a mixed solution of 3-carboxypropyltrimethoxysilane, ethanol and acetone, stirring for 1.6-3.4 hours and then filtering, washing the filtered product with sufficient deionized water, and drying the washed product at 30° C. to obtain pretreated blast furnace slag; The polyvinyl alcohol particles are selected from polyvinyl alcohol particles that have passed through a 150-200 mesh sieve; Wherein, the geopolymer adsorbent is prepared by the following method: S1, mixing pretreated calcium carbonate, pretreated blast furnace slag and polyvinyl alcohol particles to obtain a mixture; S2, ultrasonically dispersing nano-silicon dioxide into deionized water to obtain silica sol, dissolving sodium hydroxide into deionized water to obtain sodium hydroxide solution, adding the sodium hydroxide solution to the silica sol, and continuously stirring for 18-26 hours to obtain an alkaline excitation solution, wherein the mass ratio of nano-silicon dioxide to deionized water in the silica sol is 1:(3-5), and the mass ratio of sodium hydroxide to deionized water in the sodium hydroxide solution is 1:(6-8); S3, adding the mixture obtained in step S1 to the alkali stimulating solution in step S2 to obtain an alkali stimulating product, stirring the alkali stimulating product at high speed for 1-3 minutes and then adding it to the mold; S4, drying the alkali-activated substance in the mold in step S3 to obtain a dried product; S5. Soak the mold containing the dried product in step S4 in a 0.2 mol / L hydrochloric acid solution, take the mold out of the hydrochloric acid solution, separate the mold, wash the material in the mold with sufficient deionized water, and obtain the geopolymer adsorbent after natural drying.

2. The geopolymer adsorbent according to claim 1, characterized in that The mass ratio of the 3-(2,3-epoxypropoxy)propyltrimethoxysilane, the calcium carbonate particles and the chloroform is 1:(2-5):(60-100).

3. The geopolymer adsorbent according to claim 1, characterized in that: The mass ratio of 3-carboxypropyltrimethoxysilane, blast furnace slag, ethanol and acetone is 1:(2-5):(20-40):(30-40).

4. The geopolymer adsorbent according to claim 1, characterized in that The rotation speed of continuous stirring in step S2 is 80 r / min, and the rotation speed of high-speed stirring in step S3 is 300 r / min.

5. The geopolymer adsorbent according to claim 1, characterized in that: The drying temperature in step S4 is 50-60°C.

6. The geopolymer adsorbent according to claim 1, characterized in that In step S5, the hydrochloric acid solution is heated to 60-90° C., and the mold containing the dried product is immersed in the hydrochloric acid solution for 0.5-2 hours.

7. Use of the geopolymer adsorbent according to any one of claims 1 to 6 in the treatment of zinc-containing wastewater.

Citation Information

Patent Citations

  • Geopolymer molecular sieve, preparation method and application

    CN112850726A